Liver microphysiological platforms for drug metabolism applications - Kurmangaliyeva, Akbota; Kulsharova, Gulsim (Wiley, 2021)
Abstract Drug development is a costly and lengthy process with low success rates. To improve the efficiency of drug development, there has been an increasing need in developing alternative methods able to eliminate toxic compounds early in the drug development pipeline. Drug metabolism plays a key role in determining the efficacy of a drug and its potential side effects. Since drug metabolism occurs mainly in the liver, liver cell‐based alternative engineering platforms have been growing in the last decade. Microphysiological liver cell‐based systems called liver‐on‐a‐chip platforms can better recapitulate the environment for human liver cells in laboratory settings and have the potential to reduce the number of animal models used in drug development by predicting the response of the liver to a drug in vitro. In this review, we discuss the liver microphysiological platforms from the perspective of drug metabolism studies. We highlight the stand‐alone liver‐on‐a‐chip platforms and multi‐organ systems integrating liver‐on‐a‐chip devices used for drug metabolism mimicry in vitro and review the state‐of‐the‐art platforms reported in the last few years. With the development of more robust and reproducible liver cell‐based microphysiological platforms, the drug development field has the potential of reducing the costs and lengths associated with currently existing drug testing methods.
Keywords: Microfluidics; Materials science; Internal medicine; Nanotechnology; Medicine; Pharmacology; Biology; Liver cell; Organ-on-a-chip; Drug; Drug metabolism; Drug development